Digital Literacy and Higher-Order Thinking Skills of Pre-Service Physics Teachers in Artificial Intelligence-Based Learning Management Systems - Hikmawati Hikmawati; Muhammad Taufik; Fathurrahman (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
This study aimed to investigate the levels of digital literacy and higher-order thinking skills (HOTS) among pre-service physics teachers in Artificial Intelligence (AI)-based Learning Management Systems (LMS). A descriptive quantitative approach was employed involving 54 fifth-semester students of the Physics Education Study Program, Faculty of Teacher Training and Education, University of Mataram, during the 2025/2026 academic year. Data were collected throughout the learning process from August to October 2025. The research instruments consisted of a HOTS test comprising five essay questions scored on a scale of 0–4 and a digital literacy questionnaire consisting of 36 items measured using a five-point Likert scale. The data were converted into percentages and analyzed using descriptive statistics and Spearman’s rho correlation. The results revealed that the mean HOTS score was 78.43, categorized as high, while the mean digital literacy score was 83.28, categorized as very high. HOTS scores ranged from 65.00 to 90.00, whereas digital literacy scores ranged from 72.00 to 95.00. Spearman’s rho analysis indicated a very strong positive correlation between HOTS and digital literacy (ρ = 0.941, p < 0.001). These findings suggest that higher levels of digital literacy are associated with better higher-order thinking skills among pre-service physics teachers in AI-based LMS environments.